Member of the Coordinating Committee, Head of the Team for Academics - Kyranou, Maria (My University, 2026)
The Learning Development Network was formed under the auspices of the Counselor to help students, academics and staff to adjust to mixed and online learning due to the epidemic. It's contribution to the above was achieved with seminars, online support, and useful material provided in an ongoing bases.